Mechanical behavior of flexible pavements due to the suspension-tread tire vehicle load transmission system (2019)
In this research, we evaluated the mechanical behavior of a flexible pavement for roads with low-traffic volume due to the vehicular load transmission system of suspension-tire treadusing3D-Move Analysis V2.1 software, which models using a continuum-based finite-layer approach. Weslea 3.0 elastic multplayer software was used for validation. The results led to conclude that if carefully observed, the tensilestrain in the lower fibers of the asphalt layer of the flexible pavement studied are higher in the proposed modelsof elastic-suspension-tire tread-road roughness and viscoelasticsuspension-tire tread-road roughness, which have a range of change percentage from 6.59% to 17.19% compared with the analytical validation modeling, indicating a possible under-sizing of the asphalt layers. Furthermore, according to the models proposed of elastic-suspension-tire tread-road roughness and viscoelastic-suspension-tire tread-road roughness, the additional parameters of the suspension-tire tread system interfere in the behavior of the asphalt layer of the flexible pavement studied, because if the roughness of the pavement increases, the perturbation of the suspension system and the tensilestrain in the lower fibers of the asphalt layer also increase; as shown in the results of the change percentages related to analytical validation modeling (Weslea 3.0), from 13.83% (model elastic-roughness average) to 17.19% (model elasticroughness rough), and 9.54% (model viscoelastic-roughness average) to 13.04% (model viscoelastic-roughness rough). © 2006-2019 Asian Research Publishing Network (ARPN).